Study on health seeking behaviour of elderly population for chronic diseases in a rural area of northern Kerala - Rajeev, Krishnaraj; K. K., Ashwin Raj; Suresh, Atul; Salim, Ashid (International Journal of Research in Medical Sciences, 2023)
Background: The existing global and national demographic structure is evolving towards a greater number of elderly people. Chronic diseases have negative personal, societal, and financial consequences in all communities and economies. Health seeking behaviour is thought to be the result of a complicated interplay between the patient's disease condition and socioeconomic and demographic variables, as well as the quality, availability, and accessibility of healthcare services. Methods: Community based cross sectional study was carried out among the persons aged 60 years or above who had one or more chronic disease residing in rural area of Malappuram district, Kerala. Data was collected from 240 participants by interview method using a pre-designed questionnaire. Results: Hypertension, dyslipidemia, and diabetes mellitus were the three diseases that affect elderly individuals most frequently. Majority (86.7%) of the study population is seeking medical care for chronic conditions. 82.1% of the population prefer modern medicine and 5.8% prefer AYUSH system of medicine. Age, marital status, education, and occupation were all factors that contributed to their health-seeking behaviour. Conclusions: Immediate attention and action are required from the health care authorities and policymakers to reinforce the geriatric healthcare strategy and enhance the behaviour of people seeking health care for chronic diseases.